Investigation of origination and development of the surface deformation relief of crystalline materials by laser radiation - Badiyan, E.E.; Tonkopryad, A.G.; Shekhovtsov, O.V.; Shurinov, R.V.; Zetova, T.R.; Kazachkova, K.S. (Functional Materials, 2015)
In the paper we present the results of the experimental studies of structure of the deformation relief in the form of steps at the exit site of dislocations on polished surface of polycrystalline specimen of aluminum during plastic deformation. It is shown that, despite quasiperiodicity of such structure which is characterized by different values of the grating period and the curved slip lines forming the grate, it leads to diffraction of the laser radiation on it. The analysis of the diffraction patterns obtained in situ during deformation allows us to trace the evolution of the deformation structures. It is experimentally shown that the origination of the dislocation slip in the early stages of plastic deformation can be detected and the direction of slip and change of this direction during plastic deformation can be determined by using the diffraction patterns. The minimal distance between the slip lines which characterize intensive development of the dislocation slip can be detected by the diffraction patterns. Thus the intensity of plastic deformation at all stages can be studied.